2012
DOI: 10.1136/bmjspcare-2012-000196.142
|View full text |Cite
|
Sign up to set email alerts
|

Symptom management and its barriers among patients with terminal advanced cancer in Thailand

Abstract: Aims Effective symptom management is important part of end of life care. It is aimed at improving the quality of dying. The findings presented in this conference are taken from a larger project, the aim of which was to explore the experience of patients living with terminal cancer in southern, Thailand. This presentation reports on one of the main themes under this study's investigation; symptom management and its barriers. Method A longitudinal qualitative study was conducted. Fifteen patients who had been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[ 5 ] Nilmana et al . [ 6 ] and Harding et al . [ 7 ] reported in their study that most of the cancer patients had pain (87.5%), lack of energy (77.7%), feeling sad (75.9%), feeling of drowsiness (72.3%) and worry (69.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Nilmana et al . [ 6 ] and Harding et al . [ 7 ] reported in their study that most of the cancer patients had pain (87.5%), lack of energy (77.7%), feeling sad (75.9%), feeling of drowsiness (72.3%) and worry (69.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that barriers to symptoms management were: Worry about side effect (71.4%), fear of addiction (23.1%) and pain medication harm the immune system (89.0%). Similar findings on barriers were observed by Nilmana et al .,[ 6 ] Edrington et al . [ 9 ] and Ward et al .…”
Section: Discussionmentioning
confidence: 99%
“…6 87.5% of cancer patients reported pain in another study by Nilmana et al 7 Pain results either from illness and its treatment or cooccurring illnesses. Increase in the intensity of pain is usually seen in the last four months before death and it is linked to nociceptive or neuropathic mechanisms or both pain types.…”
Section: Discussionmentioning
confidence: 98%